Quantum confinement of the Dirac surface states in topological-insulator nanowires - Felix Münning (Nature Portfolio, 2021)
In topological insulator nanowires quantized Dirac sub-bands are expected, but direct evidence is still missing. Here, the authors report signatures of sub-bands in the gate-voltage dependence of the resistance by tuning the chemical potential in (Bi1−xSbx)2Te3 nanowires through the Dirac point.